2019
DOI: 10.4018/jeco.2019100101
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Risk Aversion on Adoption of IT and Mobile Platforms on P&C Insurance Demand

Abstract: This article studies the comparative efficiency of information communication technology (ICT)-enabled platforms in the property and casualty (P&C) domain by studying moderating role of risk aversion. This slow rate of ICT-enabled channel in property and casualty insurance (PCI) domain does not gain ample attention in the extant literature. The present article argues that the impact of ICT enabled platforms may have different outcomes on PCI consumption due to moderating role of risk aversion. In insurance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…The results also support that risk-taking moderated the relationship between brand image and purchase intention (Hypothesis 2a) and the multiplicative effect of WOM, risk-taking, and brand image (Hypothesis 2b), and these findings are in line with available empirical evidence about direct relationships (Li et al. , 2016; Tiwari et al. , 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results also support that risk-taking moderated the relationship between brand image and purchase intention (Hypothesis 2a) and the multiplicative effect of WOM, risk-taking, and brand image (Hypothesis 2b), and these findings are in line with available empirical evidence about direct relationships (Li et al. , 2016; Tiwari et al. , 2019).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, there is ample evidence from the literature that WOM (positive and negative feedback about products) reduces or increases the risk perceptions about the products that may influence purchase decisions (Murphy et al, 2007;Nguyen et al, 2021;Rajaobelina et al, 2021;Song et al, 2021). Thus, risk-taking consumer favors counterfeit products (Azemi et al, 2022), whereas the WOM may play a critical role in altering the moderating effect of risk-taking on consumer behavior (Ahmad, 2020;Allen et al, 2005;Li et al, 2016;Sicilia et al, 2016;Tiwari et al, 2019). Therefore, it would be interesting to examine the multiplicative effect of WOM and risktaking behavior in counterfeit brands, which remained under-researched areas in literature.…”
Section: Counterfeit Brand Shoesmentioning
confidence: 99%
“…However, the high cost of health insurance remains a significant challenge that limits the effectiveness of these products for the public. Studies have identified market inefficiencies as the main cause of high health insurance costs, which stem from inadequate information exchange [5,2,7,9]. To capture the customer information, the products may be made or updated several times in response to changes in the risk profile of the insured.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, health insurers must ascertain how to deliver both value and quality. To do so, firms have been employing advance ITenabled solutions and employing them at various stages of the insurance value chain [6][7][8]. The level of technology integration is rising every year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation